Influences of roaming domestic cats on wildlife activity in patchy urban environments - Fardell, Loren L.; Pavey, Chris R.; Dickman, Christopher R. (Frontiers in Ecology and Evolution, 2023)
Roaming domestic cats (Felis catus) are recognised as a threat to wildlife globally. Yet management of pet cats in urbanised areas is not regularly mandated, and management of feral cats in urbanised areas is rarely implemented. Mounting evidence emphasises the value of urban environments as hot spots of wildlife activity, which as the human population continues to grow may become the best or only habitats available to some wildlife species. Wildlife in urban environments must navigate introduced stressors that can compound with natural stressors. Additional, often novel, predators such as free-roaming pet and feral cats that are prevalent in urban environments could have high nonconsumptive fear/stress impacts on urban wildlife that influence their activity and adversely affect their health and reproduction capabilities, possibly more so than direct predation effects do. Cat roaming activity, particularly that of pet cats, could be managed with the support of the community, though motivation needs to be ensured. Understanding if roaming cat activity influences urban wildlife activity via perceived fear/stress impacts will help to build community motivation for the need for domestic cat management in urbanised areas. Using infrared motion sensor cameras positioned in both yards and green space edge habitats, we observed whether the presence and times active of native and introduced small mammals, and native birds, were impacted by domestic cat activity within a 24-h period and by their activity in the prior-24-h period. We found evidence of cat roaming activity during the hours of most wildlife activity, and show that wildlife navigated ‘landscapes of fear’ relative to cat activity, as wildlife observed across a 24-h period increased their activity in the absence of cats in the same 24-h period and in the previous 24-h period. We also tested if cat activity was relative to previous cat activity, or disturbances, and found that cats reduced activity in response to each, but were still consistently present. Our results provide justification for the need to increase management of domestic cats in urbanised areas and offer fear/stress impacts as a novel approach to engender community support of such management.